Local factors dominantly influence citrus red mite (Panonychus citri (McGregor)) population over landscape factors in Indonesian citrus orchards: Faktor lokal lebih dominan mempengaruhi populasi tungau merah jeruk (Panonychus citri (McGregor)) daripada faktor lanskap pada pertanaman jeruk di Indonesia - Salamah, Luklu Is; Rizali, Akhmad; Puspitarini, Retno Dyah (Jurnal Entomologi Indonesia, 2025)
The citrus red mite Panonychus citri (McGregor) is a major pest that can reduce the quality and yield of citrus crops. However, information regarding the local and landscape factors that influence its population dynamics remains limited. This study aimed to analyse the influence of local and landscape factors on citrus red mite population density. The research was conducted in nine citrus orchards in Malang, East Java, Indonesia. Data collected included local factors (pesticide application frequency and plant canopy density) and landscape factors (landscape composition, encompassing the number of patches (NP) and class area (CA) of semi-natural habitats). Pesticide application frequency data were obtained through farmer interviews, while canopy density was measured using a photographic method and analysed with ImageJ2 software. Landscape composition data were by digitizing land-use types within a 500-meter radius of the plot center using QGIS software and subsequently analysed using LecoS (QGIS add-ins) to obtain the NP and CA of semi-natural habitats. The generalized linear  model (GLM) analysis indicated no overall significant influence of both local and landscape factors on P. citri population density. However, it was found that the variation in mite population density was significantly influenced by citrus plant canopy density. These findings suggest that local factors, particularly the canopy microhabitat conditions, are more critical in affecting the P. citri population compared to landscape factors. Therefore, the management strategy for citrus red mite should be focused on the local, on-farm scale.